The Problem of The Position of Natural Person in The Process of Bankruptcy in The Context of European Integrations (Vallis Aurea, 2023)
Individual bankruptcy, as a procedure of preferential bankruptcy procedure reserved for natural person, often leads to problems in application, which are a consequence of not understanding theessence of the institute or often bad implementation of application instruments, where all of this then leads to paradoxical inability to apply the institute. This paper will emphasize the basic problems which appear when the subject of the bankruptcy procedure is a natural person. Author will analyze it through the problem of insolvency of individuals and factual inability to realize payment of creditors. It will be analyzed based on the following aspects: this matter is unregulated in Serbian law; then a comparative overview of the issue of the position of an insolvent artisan in Croatian law, and the issue of abuse of rights which are used by the citizens of EU through the institute “bankruptcy tourism”. Based on this comparative analysis, the author will try to provide suggestions with the goal of progress of at least partial payment of the creditors by the individual debtor in the bankruptcy process. This Article will provide specific suggestions which the future legislation of Serbia should deal with, and which will be based on the critical overview of the foreseeninstitute of individual bankruptcy in Croatian law, which is not used in practice.